Pregnancy in overweight women – the impact of some biological and social determinants - Vidin Kirkov; Valentina Petkova; Dobriana Sidjimova; Lilia Koleva; Emilia Naseva; Milen Dimitrov (Pharmacia)
Obesity is one of the risk factors for the development of socially significant diseases from the group of chronic non-communicable diseases, and obesity in women of reproductive age and in particular in pregnant women is an extremely important medico-social problem affecting both the mother and her child, and indeed all of modern society. In this article, the influence of some biological and social determinants influencing this medico-social problem, leading to changes in the trends of medico-demographic health indicators serving to assess public health, will be examined and analyzed.